Mechanistic insights into Pin1 peptidyl‐prolyl cis‐trans isomerization from umbrella sampling simulations. Issue 11 (11th August 2014) - Di Martino, Giovanni Paolo; Masetti, Matteo; Cavalli, Andrea; Recanatini, Maurizio
ABSTRACT The peptidyl‐proyl isomerase Pin1 plays a key role in the regulation of phospho(p)‐Ser/Thr‐Pro proteins, acting as a molecular timer of the cell cycle. After recognition of these motifs, Pin1 catalyzes the rapid cis‐trans isomerization of proline amide bonds of substrates, contributing to maintain the equilibrium between the two conformations. Although a great interest has arisen on this enzyme, its catalytic mechanism has long been debated. Here, the cis‐trans isomerization of a model peptide system was investigated by means of umbrella sampling simulations in the Pin1‐bound and unbound states. We obtained free energy barriers consistent with experimental data, and identified several enzymatic features directly linked to the acceleration of the prolyl bond isomerization. In particular, an enhanced autocatalysis, the stabilization of perturbed ground state conformations, and the substrate binding in a procatalytic conformation were found as main contributions to explain the lowering of the isomerization free energy barrier. Proteins 2014; 82:2943–2956. © 2014 Wiley Periodicals, Inc.